2021
DOI: 10.1111/pan.14319
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for children with anterior mediastinal masses

Abstract: Children with an anterior mediastinal mass may have cardiopulmonary compromise that can be exacerbated under general anesthesia. Signs and symptoms such as cough, shortness of breath, stridor, orthopnea, accessory muscle use, a history of respiratory arrest, and the presence of a pleural effusion and upper body edema are predictive of perioperative complications. A larger mediastinal mass on imaging is predictive of perioperative complications. Risk stratification of patients, together with an individualized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Evaluation of airway compression by the anterior mediastinal mass is important for subsequent surgical biopsy [ [2] , [3] , [4] , [20] , [21] , [22] ]. General anesthesia should be avoided in patients with severe airway compression [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of airway compression by the anterior mediastinal mass is important for subsequent surgical biopsy [ [2] , [3] , [4] , [20] , [21] , [22] ]. General anesthesia should be avoided in patients with severe airway compression [20] .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of long tracheal stenosis (for example extra-luminal compression by a mediastinal mass), placement of a rigid bronchoscope might be required. This enables navigation through the narrow region while splinting the airway open, and at the same time allowing ventilation via a side port 78,91–95 . The main limitation of rigid and semirigid scopes is possible difficulty in aligning the oral and tracheal axes, for example in cases of severely restricted mouth opening or severely restricted retroflexion of the head 96–98 .…”
Section: Methodsmentioning
confidence: 99%
“…This enables navigation through the narrow region while splinting the airway open, and at the same time allowing ventilation via a side port. 78,[91][92][93][94][95] The main limitation of rigid and semirigid scopes is possible difficulty in aligning the oral and tracheal axes, for example in cases of severely restricted mouth opening or severely restricted retroflexion of the head. [96][97][98] A trial including 26 children (12 of them infants) with difficult airway reported quicker intubation with a semirigid scope than with a fibreoptic scope (52 vs. 83 s) (Supplementary Table S15, http://links.lww.com/EJA/A891).…”
Section: Pico 4 Difficult Airway Managementmentioning
confidence: 99%
“…We read with interest the article by Tan and colleagues entitled "Anesthesia for children with anterior mediastinal masses" published in Pediatric Anesthesia. 1 They provided a thorough guide to the risk stratification and individualized anesthetic and surgical operative management for such patients. They recommend avoidance of general anesthesia when possible and maintenance of spontaneous ventilation if general anesthesia is necessary.…”
Section: Response To "Anesthesia For Children With Anterior Mediastin...mentioning
confidence: 99%
“…Tan and colleagues describe neuromuscular blockade as causing "smooth muscle relaxation, a loss of airway muscle tone, and further worsen[ing] airway compression". 1,2 However, the reference used to explain this effect attributes the airway smooth muscle relaxation to general anesthesia and not neuromuscular blockade. Neuromuscular blockade can enhance collapse of the bronchi, trachea, or external vessels when there is "loss of tone of the supporting musculature of the chest wall, neck, and supraglottic airway".…”
Section: Response To "Anesthesia For Children With Anterior Mediastin...mentioning
confidence: 99%